Performance of front line demonstrations on sunflower (Helianthus annuus L.) under rainfed conditions of Chamarajanagara district Karnataka state: PERFORMANCE OF FLDs ON SUNFLOWER UNDER RAINFED CONDITIONS OF KARNATAKA STATE - C M SUNIL; CHANDRAKALA HANAGI; G S YOGESH (Journal of Oilseeds Research, 2023)
Sunflower is an important oilseed crop of Karnataka. It plays a major role in increasing the income of small and marginal farmers of Southern Karnataka. The production of sunflower in Chamarajanagara district is very less compared to state and national average. The ICAR-Krishi Vigyan Kendra, Chamarajanagara district conducted 90 frontline demonstrations on sunflower covering an area of 36 ha of farmers’fields in villages viz., Kotamballi and Taggaluru during the year 2019 and 2020 to showcase latest production technologies in comparison with farmer’s practice. Demonstrated technologies comprised short duration hybrid KBSH-78, recommended seed rate, sowing method, nutrient management, pest and disease management, and adoption of whole package of practices for the crop. The study revealed that the demonstrated technology recorded a mean yield of 996 kg/ha which was 235.35% higher than that obtained with farmers’ practice (297 kg/ha). Higher benefit: cost ratio of 1.41 was obtained with improved technologies in comparison to farmers’ practices (0.48). Therefore, there is a need to disseminate the improved technologies among the farmers with effective extension methods like training and demonstrations. The farmers should be encouraged to adopt the recommended package of practices for realizing higher returns.